2010
DOI: 10.1007/s10552-010-9513-x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and risk of breast cancer in Mexican women

Abstract: BACKGROUND-Little is known about the relationship between alcohol intake and breast cancer risk among Mexican women. This association may be modified by folate and Vitamin B12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…Larsson et al (2010) and Cui et al (2008) reported an increased risk of double RH-tumors associated with the consumption of beta carotenes, which the former research team attributed to the fact that such elevated consumption is more common in smokers (Cui et al, 2008;Larsson et al, 2010). Similarly, Beasley et al (2010) in Mexico followed the line of research begun by Lajous et al (2006), and confirmed that alcohol consumption is associated with lower levels of folates, which in turn increases the risk of breast cancer (Lajous et al, 2006;Beasley et al, 2010).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Larsson et al (2010) and Cui et al (2008) reported an increased risk of double RH-tumors associated with the consumption of beta carotenes, which the former research team attributed to the fact that such elevated consumption is more common in smokers (Cui et al, 2008;Larsson et al, 2010). Similarly, Beasley et al (2010) in Mexico followed the line of research begun by Lajous et al (2006), and confirmed that alcohol consumption is associated with lower levels of folates, which in turn increases the risk of breast cancer (Lajous et al, 2006;Beasley et al, 2010).…”
Section: Discussionmentioning
confidence: 90%
“…In Mexico studies have shown that a high consumption of vitamin B12 is associated with a lower risk of breast cancer (Cox et al, 2011), while alcohol consumption and low levels of folates is related to an increased risk (Lajous et al, 2006), although it is polemic (Liu et al, 2013;Liu et al, 2014b). Studies in Mexico have also indicated a probable association between alcohol consumption and polymorphisms of the FGFR2 gene that increase the risk of breast cancer (Beasley et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22]48,49 We previously reported a modest nonsignificant increase in breast cancer risk among Mexican women who were ever drinkers (OR 1.25, 95% CI 0.99-1.58). 21 In the present analyses, adjustment for alcohol changed the point b Models are adjusted for age, study, history of alcohol consumption, menopausal status, parity, education, family history of breast cancer, and BMI at referent year; study is only included when modeling U.S. Hispanic/NA women; the referent group for all models is ''never smoked.'' CI, confidence interval; OR, odds ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between alcohol consumption and risk of breast cancer has been examined in a few studies that included Hispanic women. [20][21][22] While some results have shown that recent alcohol consumption increases breast cancer risk, 23 the combined effects of smoking and alcohol with breast cancer are yet to be fully illuminated. It is biologically plausible that obesity and alcohol consumption may modify the susceptibility of breast tissues to tobacco carcinogens.…”
mentioning
confidence: 99%
“…Over the last few years, the incidence rates of breast cancer have increased in most countries. Several studies have found that the development of breast cancer is possibly associated with tobacco, alcohol consumption and other environmental factors (2,3). Furthermore, interindividual differences, including single-nucleotide polymorphisms, may affect protein activity and alter the susceptibility to developing breast cancer.…”
Section: Introductionmentioning
confidence: 99%